Perancangan Aplikasi Repository Skripsi Berbasis Web - Triwardana, Ravly; Faisal, Ilham; Lubis, Imran (Universitas Islam Negeri Sumatera Utara, 2022)
Repository is a place to accommodate a collection of scientific works, including a final project or thesis, currently a repository is needed by the academic community of a university, the repository is also known as a digital library. The purpose of designing this application is to make it easier for students to find references to scientific works that have been completed by alumni into a web-based thesis repository application. The application design process is carried out using the PHP programming language and mysql database. The results of this study are in the form of a web-based thesis repository application design that can be accessed by all students on any type of device very easily, anytime and anywhere through a browser connected to the internet network. By designing this application, it is hoped that it can prevent data loss, damage, and is useful for all students and makes it easier to find the desired information. In designing this application using appserv 8.6 in designing the Website and also this application is designed using a system that can make it easier for users to access the application. Keywords: Repository, Web, Appserv, PHP, MySql